¿Qué significa una ‘microbiología para el desarrollo sostenible’? (2018)
ABSTRACT: The quest for sustainable development as a purpose of microbiology has at least two implications: i) research in microbiology has the ultimate aim of leading societies to reach the convergence of economic prosperity, social wellbeing and environmental protection and, ii) microorganisms should be used to improve the social-ecological adaptability of human activities. The current state of research in microbiology related to sustainable development shows that studies have focused on challenges in the field of agriculture, livestock, and energy production, and in fields where microorganisms have diverse uses such as ecosystems monitoring, pollutant biodegradation and waste utilization (by-product generation). However, despite all these uses being essential for microbiology to contribute to sustainable development, it is necessary to resolve other problems not easily detectable in studies related to microbiology development. There are, at least, three challenges: firstly, the exploration of micro-biodiversity in order to provide more alternatives of transformation for industrial activities; secondly, the sustainability analysis of those human activities that have already included microbial technologies to make them more sustainable; and thirdly, the need to train microbiologists on sustainable development.